PENGARUH ONLINE CUSTOMER REVIEW, CONTENT MARKETING DAN PRODUCT KNOWLEDGE TERHADAP KEPUTUSAN PEMBELIAN E-COMMERCE TOKOPEDIA: (Studi Empiris Pada Generasi Z di Kecamatan Bangsri) - Listiani, Agnes Eva; Arifin, Samsul (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aims to find out how Online Customer Reviews, Content Marketing, and Product Knowledge influence Tokopedia E-Commerce Purchase Decisions among Generation Z in Bangsri District. The population of this research is Generation Z in Bangsri District, with 100 respondents calculated using the Slovin Formula. Data for this research was collected through a purposive sampling method. The research results show that Online Customer Reviews (X1) have a positive and significant effect on purchasing decisions; Content Marketing (X2) has a positive and significant effect on purchasing decisions; and Product Knowledge (X3) has a positive and significant effect on purchasing decisions. Thus, it can be concluded that Online Customer Reviews, Content Marketing, and Product Knowledge all have a positive and significant impact on purchasing decisions. Keywords: Online Customer Review, Content Marketing, Product Knowledge, Purchase Decision, Generation Z